Quantitative brain sodium MRI depicts corticospinal impairment in amyotrophic lateral sclerosis - Grapperon, Aude-Marie; Ridley, Ben; Verschueren, Annie; Maarouf, Adil; Confort-Gouny, Sylviane; Fortanier, Etienne; Schad, Lothar R.; Guye, Maxime; Ranjeva, Jean-Philippe; Attarian, Shahram; Zaaraoui, Wafaa (Radiology, 2019)
BackgroundAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that mainly affects the upper and lower motor neurons. Recent sodium (23Na) MRI studies have shown that abnormal sodium concentration is related to neuronal suffering in neurodegenerative conditions.PurposeTo use 23Na MRI to investigate abnormal sodium concentrations and map their distribution in the brains of study participants with ALS as compared with healthy control subjects.Materials and MethodsTwenty-seven participants with ALS (mean age, 54 years ± 10 [standard deviation], eight women) and 30 healthy control subjects (mean age, 50 years ± 10; 16 women) were prospectively recruited between September 2015 and October 2017 and were examined by using conventional proton MRI and sodium MRI at 3 T. Voxel-based statistical mapping was used to compare quantitative whole-brain total sodium concentration (TSC) maps in participants with ALS with those in control subjects and to localize regions of abnormal elevated TSC. Potential overlap of abnormal elevated TSC with regions of atrophy as detected with 1H MRI also was investigated.ResultsVoxel-based statistical mapping analyses revealed higher sodium concentration in motor regions (bilateral precentral gyri, corticospinal tracts, and the corpus callosum) of participants with ALS (two-sample t test, P < .005; age and sex as covariates). In these regions, mean TSC was higher in participants with ALS (mean, 45.6 mmol/L wet tissue ± 3.2) than in control subjects (mean, 41.8 mmol/L wet tissue ± 2.7; P < .001; Cohen d = 1.28). Brain regions showing higher TSC represented a volume of 15.4 cm3 that did not overlap with gray matter atrophy occupying a volume of 16.9 cm3. Elevated TSC correlated moderately with corticospinal conduction failure assessed with transcranial magnetic stimulation in the right upper limb (Spearman ρ = −0.57; 95% confidence interval: −0.78, −0.16; P = .005; n = 23).ConclusionQuantitative 23Na MRI is sensitive to alterations of brain sodium homeostasis within disease-relevant regions in patients with amyotrophic lateral sclerosis (ALS). This supports further investigation of abnormal sodium concentration as a potential marker of neurodegenerative processes in patients with ALS that could be used as a secondary endpoint in clinical trials.© RSNA, 2019Online supplemental material is available for this article.
Gesehen am 17.01.2020